Management of Acute Cerebral Infarction by Intravenous Thrombolysis with Recombinant T Cell Receptor and Plasminogen Activator and Association of Emergency Nursing Route in the Prognosis: Recombinant T Cell Receptor for Acute Cerebral Infarction - Yuqi Liu,; Chengyong Wang,; Yuanpeng Han, (Cellular and Molecular Biology, 2023)
The purpose of this study is to determine the impact and prognosis of the emergency nursing approach in conjunction with the use of recombinant T cell receptors and plasminogen activators in patients who have just had an acute stroke. In this study, 100 patients were randomly selected that were equally divided into experimental and control groups. The period of hospital admission, the results of the Montreal Cognitive Assessment (MoCA) and the Mini-mental State Examination (MMSE), the results of the Glasgow Outcome Scale (GOS), and the results of the Activities of Daily Living were all analysed before and after the intervention.. Both the amount of time it took to get a diagnosis after being admitted and the amount of time it took to receive specialised therapy after receiving a diagnosis were significantly reduced in the observation group (both P values less than 0.05). At one month after discharge, the scores of ADL, MoCA, MMSE, and GOS rose in both groups, with more significant changes occurring in the observation group (all P<0.05). This was due to the fact that ADL scores declined while scores for MoCA, MMSE, and GOS increased. The percentage of people who were disabled in the observation group was significantly lower than the percentage in the control group (P<0.05). Including emergency, nursing might drastically reduce the time it takes for patients with acute stroke to be admitted and begin receiving specialised care.